Up-to-date technologies of producing reinforced concrete constructions in transport industry - Клімов, Ю. А.; Крівєльов, Л. І. (Proceedings of National Aviation University (archive), 2000)
Presented is the analysis of the works at XIII Congress of International Federeation of prereinforced concrete construction (FIP). Scientific researches and technical solutions of reinforced concrete constructions realized in the developed countries have determined the main trends in perfection of concrete constructions in the next century (perfection of data on quality of constructive solutions of reinforcement with on-metallic fibrous materials, energy saving technologies of concrete production, development and investigation of perspective technical solutions)